Breast cancer subtypes in Australian Chinese women. Issue 12 (15th September 2020) - Hong, Alton; Chua, Jonathan; Cheng, Michael; Law, Michael
Abstract: Background: It has been suggested that Chinese patients with breast cancer present at a younger age compared to the general Australian population, with tumour pathological characteristics that carry less favourable outcomes. This study was aimed to investigate if a substantial difference in breast cancer subtypes exists between the Australian Chinese population and the general Australian population. Methods: All patients with breast cancer treated by two of the authors (consultant breast surgeons) at Eastern Health, Victoria between 2010 and 2016 were identified through the BreastSurgANZ Quality Audit database. Australian Chinese patients were further identified through outpatient records and registration information. Medical histories were examined to obtain patient demographics, tumour characteristics and outcome. Patient and tumour characteristics between the Australian Chinese population were then compared to the general Australian population. Results: A total of 97 Australian Chinese patients with breast cancer were identified out of 582 patients. Mean age at diagnosis was 56.7 years, approximately 6 years younger than the general Australian population. There was a statistically significant difference in incidence of Luminal A tumours with 25 patients (25.77%) from the Chinese group affected compared to 310 patients (63.92%) from the general group ( P  < 0.001). There was no significant difference in proportions of the other tumour subtypes between the two groups. Conclusion: Australian Chinese breast cancer patients present at a younger age compared to the general Australian population, with a smaller proportion of patients having Luminal A tumours. Abstract : It has been suggested that Chinese patients with breast cancer present at a younger age compared to the general Australian population, with tumour pathological characteristics that carry less favourable outcomes. This study was aimed to investigate if a substantial difference in breast cancer subtypes exists between the Australian Chinese population and the general Australian population.